#### Answer

x=0

#### Work Step by Step

Simplifying
-6(x + -5) + 3x = 6x + -10(-3 + x)
Reorder the terms:
-6(-5 + x) + 3x = 6x + -10(-3 + x)
(-5 * -6 + x * -6) + 3x = 6x + -10(-3 + x)
(30 + -6x) + 3x = 6x + -10(-3 + x)
Combine like terms: -6x + 3x = -3x
30 + -3x = 6x + -10(-3 + x)
30 + -3x = 6x + (-3 * -10 + x * -10)
30 + -3x = 6x + (30 + -10x)
Reorder the terms:
30 + -3x = 30 + 6x + -10x
Combine like terms: 6x + -10x = -4x
30 + -3x = 30 + -4x
Add '-30' to each side of the equation.
30 + -30 + -3x = 30 + -30 + -4x
Combine like terms: 30 + -30 = 0
0 + -3x = 30 + -30 + -4x
-3x = 30 + -30 + -4x
Combine like terms: 30 + -30 = 0
-3x = 0 + -4x
-3x = -4x
Solving
-3x = -4x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '4x' to each side of the equation.
-3x + 4x = -4x + 4x
Combine like terms: -3x + 4x = 1x
1x = -4x + 4x
Combine like terms: -4x + 4x = 0
1x = 0
Divide each side by '1'.
x = 0
Simplifying
x = 0